Coordination of Hours within the Firm - Claudio Labanca; Dario Pozzoli (Institute of Labor Economics (IZA), 2018)
Although coworkers are spending an increasing share of their working time interacting with one another, little is known about how the coordination of hours among heterogenous coworkers affects pay, productivity and labor supply. In this paper, we use linked employer-employee data on hours worked in Denmark to first document evidence of positive correlations between wages, productivity and the degree of hours coordination – measured as the dispersion of hours – within firms. We then estimate labor supply elasticities by exploiting changes made to the personal income tax schedule in 2010. We find that hours coordination is associated with attenuated labor supply elasticity and spillovers on coworkers not directly affected by the tax change. These spillovers lead to a 3.3% decrease in tax revenues from the 2010 tax reform, and if ignored, they induce substantial downward bias in estimates of the labor supply elasticity. We explain these findings in a framework in which differently productive firms choose whether to coordinate hours in exchange for productivity gains, leading more productive firms to select into coordinating hours and to pay compensating wage differentials.
Keywords: J31; H20; J20; 330; coordination; working hours; labor supply elasticity; productivity